2010
DOI: 10.1007/s13197-010-0015-3
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic and antioxidant efficacy of dehydrated onion in experimental rats

Abstract: Hypolipidemic and antioxidant potency of a dehydrated onion product was evaluated in experimental rats maintained for 6 weeks at 5 and 10% dietary levels. Serum cholesterol especially low-density lipoprotein was signifi cantly reduced by dietary dehydrated onion in hypercholesterolemic rats. This was associated with an increase in high density lipoprotein cholesterol. Blood triglyceride concentration in hypercholesterolemic rats was lower in onion supplemented diet group. Glutathione, ascorbic acid and α-tocop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…Dehydrated onion, at 5 or 10% inclusion level, showed cholesterol-lowering and antioxidant effects in hyper-cholesterolemic experimental rats (Vidyavati et al, 2010). Histological and biochemical studies using suitable dosage of garlic according to the body weight found positive effects of different in-feed garlic extracts on hepatic coccidiosis in infected rabbits (Toulah and Al-Rawi, 2007), as well as cholesterol levels of blood and oxidative status of the hepatic tissue in cholesterol-fed rabbits, treated with 1,5 mL/kg day of garlic extract for 3 mo (Arhan et al, 2009).…”
Section: Digestarommentioning
confidence: 95%
“…Dehydrated onion, at 5 or 10% inclusion level, showed cholesterol-lowering and antioxidant effects in hyper-cholesterolemic experimental rats (Vidyavati et al, 2010). Histological and biochemical studies using suitable dosage of garlic according to the body weight found positive effects of different in-feed garlic extracts on hepatic coccidiosis in infected rabbits (Toulah and Al-Rawi, 2007), as well as cholesterol levels of blood and oxidative status of the hepatic tissue in cholesterol-fed rabbits, treated with 1,5 mL/kg day of garlic extract for 3 mo (Arhan et al, 2009).…”
Section: Digestarommentioning
confidence: 95%
“…Onion juice can also be blended with other vegetable juices to drink or to produce ready-to-drink soups. It has also potential health benefits having antidiabetic, hypolipidemic, antiplatelet antithrombotic, antitumor, antiarthritic, and hypoglycemic agents arising from onion (Ali, Thomson, & Afzal, 2000;Lee et al, 2013;Vidyavati, Manjunatha, Hemavathy, & Srinivasan, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The moisture content in onions are dried for about 86% (wb) to 7% (wb) or less for effective storage and treatment. Dried onion in the form of powder or slices in expanded demand in many parts of the world (Vidyavati et al, 2010). Fresh and dried onions are important parts of the human diet because they contain large amounts of non-essential micronutrients called phytochemicals (Sharma et al, 2015).…”
Section: Introductionmentioning
confidence: 99%